2016
DOI: 10.1057/s41270-016-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Putting the geography into geodemographics: Using multilevel modelling to improve neighbourhood targeting – a case study of Asian pupils in London

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Putting the geography into geodemographics: using multilevel modelling to improve neighbourhood targeting -a case study of Asian pupils in London. AbstractThis paper explores the use of multilevel modelling to provide a statistical framework for geodemographic analysis. It argues that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Historically, Harris et al (2005) and Leventhal (2015) have suggested that businesses tended to employ less rigorous methods of determining where to locate. These included reliance on manager knowledge and intuition (Fowler, 2016), or the ability to identify obvious locations (Bas and Gulseroy, 2018).…”
Section: Research Context: the Importance Of Site Selectionmentioning
confidence: 99%
“…Historically, Harris et al (2005) and Leventhal (2015) have suggested that businesses tended to employ less rigorous methods of determining where to locate. These included reliance on manager knowledge and intuition (Fowler, 2016), or the ability to identify obvious locations (Bas and Gulseroy, 2018).…”
Section: Research Context: the Importance Of Site Selectionmentioning
confidence: 99%
“…To test RO3 (identify differences in the target audiences of payday loan locations and traditional banks at the neighborhood level), a geodemographic analysis using a factor analysis and cluster analysis will be used to calculate an index representation score. This research follows an analytical approach laid out by Harris et al (2005), Leventhal (2015), and Webber and Burroughs (2018).…”
Section: Geodemographic Analysismentioning
confidence: 99%
“…Geodemographic classifications have been developed in the UK over the past 50 years (Harris et al, 2005;Webber and Burrows, 2018), with the first model being created for the city of Liverpool in the 1970s from newly digitised census records (Webber, 1975). This model was then later expanded to the national extent (Webber, 1977;Webber and Craig, 1978), and subsequently other census-based geodemographic classifications have been created after each decennial census of the population, in 1981 (Charlton et al, 1985), 1991 (Brown and Batey, 1994), 2001 Rees, 2006, 2007), 2011 (Gale et al, 2016), and most recently 2021 (Wyszomierski et al, 2023).…”
Section: Introductionmentioning
confidence: 99%